What Factors Influence Language Impairment? Considering Resilience as well as Risk - Conti-Ramsden, Gina (Folia Phoniatr Logop, 2016)
The considerable variation observed in the profiles of children with language impairment (LI) raises challenges for the diagnosis, treatment and prevention of language difficulties, in particular since LI can present substantial issues calling for the investment of clinical, educational and public health resources. In this review paper, we examine biological, psychological and environmental factors that appear to influence the developmental course of LI. In this review paper we are interested not only in examining deficits and risk factors but also in identifying strengths of children with LI that can act as protective factors providing the child with a scaffold for more positive development and better outcomes.